Biodiversity of the aculeate wasps (Hymenoptera: Aculeata) of the Arabian Peninsula: Apoidea (Spheciformes), Ampulicidae - Gadallah, Neveen S. (Zootaxa, 2020)
An updated checklist of the Arabian species of Ampulicidae is provided here. The list includes four identified valid species in three genera and two subfamilies: Ampulicinae (2 genera, 3 species) and Dolichurinae (1 genus, 1 species). Distributions, both on the Peninsula and extra-limital, are provided for each species; of these, one (25%) is confined to the Arabian Peninsula.